If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sin(2z + i) = 2cos(2z + i) Reorder the terms: ins(i + 2z) = 2cos(2z + i) (i * ins + 2z * ins) = 2cos(2z + i) Reorder the terms: (2insz + i2ns) = 2cos(2z + i) (2insz + i2ns) = 2cos(2z + i) Reorder the terms: 2insz + i2ns = 2cos(i + 2z) 2insz + i2ns = (i * 2cos + 2z * 2cos) 2insz + i2ns = (2cios + 4cosz) Solving 2insz + i2ns = 2cios + 4cosz Solving for variable 'i'. Reorder the terms: -2cios + -4cosz + 2insz + i2ns = 2cios + 4cosz + -2cios + -4cosz Reorder the terms: -2cios + -4cosz + 2insz + i2ns = 2cios + -2cios + 4cosz + -4cosz Combine like terms: 2cios + -2cios = 0 -2cios + -4cosz + 2insz + i2ns = 0 + 4cosz + -4cosz -2cios + -4cosz + 2insz + i2ns = 4cosz + -4cosz Combine like terms: 4cosz + -4cosz = 0 -2cios + -4cosz + 2insz + i2ns = 0 Factor out the Greatest Common Factor (GCF), 's'. s(-2cio + -4coz + 2inz + i2n) = 0Subproblem 1
Set the factor 's' equal to zero and attempt to solve: Simplifying s = 0 Solving s = 0 Move all terms containing i to the left, all other terms to the right. Add '-1s' to each side of the equation. s + -1s = 0 + -1s Remove the zero: 0 = -1s Simplifying 0 = -1s The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-2cio + -4coz + 2inz + i2n)' equal to zero and attempt to solve: Simplifying -2cio + -4coz + 2inz + i2n = 0 Solving -2cio + -4coz + 2inz + i2n = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 64+64+64+64+64+64+64+64+64= | | ex=1 | | 48m-28m+12m= | | (x-2)+1+3x=5(x+1) | | 16x^2+24x+9=6 | | 12x+12=5x+96 | | 79-5x=13x+21 | | 5(x+1)-6x=3x-9 | | c-5c+7c= | | cos(x)+2x=0 | | 4x-1×(0.5)3-2x=1/8-x | | x*x+2x-23.333=0 | | 12+9x=6x | | 0.65=0.3+0.7x | | 5(x/6-x/2)-7(x/2-x/4)=9 | | 5(x/6-x/2)-80 | | x:2x+9=6 | | 30(a*a*a)*2(a*a*a*a)=1 | | (5x+3y)=360 | | 3xsquare+x-5=0 | | 4x-20=3x+8 | | 67x-4*9=0 | | (6-2x)/(6x-x^2)=0 | | mx+m=x^2+2mx+1 | | x^2+mx+1-m=0 | | -16x^3+x^2+16=0 | | z^11/7z^2 | | 3g+5d= | | 3g+5d=1 | | y=3x+4findy | | 40-x=32 | | ln(-x^2+6x)=0 |